2012
DOI: 10.1038/nsmb.2466
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary conservation of codon optimality reveals hidden signatures of cotranslational folding

Abstract: The choice of codons can influence local translation kinetics during protein synthesis. Whether codon preference is linked to co-translational regulation of polypeptide folding remains unclear. Here, we derive a revised translational efficiency scale that incorporates the competition between tRNA supply and demand. Applying this scale to ten closely related yeasts, we uncover the evolutionary conservation of codon optimality in eukaryotes. This analysis reveals universal patterns of conserved optimal and nonop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
566
7
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(604 citation statements)
references
References 50 publications
27
566
7
4
Order By: Relevance
“…In the first study, it was found that protein structure-containing coils are translated more quickly than a-helical or b-strand structures 45 . In the other study, it was found that both optimal and non-optimal codons are enriched in a-helical and b-strand structures 16 . These results are consistent with the notion that both fast-and slow-translating codons play a role in coordinating cotranslational folding; however, they do not rule out alternative hypotheses of their functional consequences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first study, it was found that protein structure-containing coils are translated more quickly than a-helical or b-strand structures 45 . In the other study, it was found that both optimal and non-optimal codons are enriched in a-helical and b-strand structures 16 . These results are consistent with the notion that both fast-and slow-translating codons play a role in coordinating cotranslational folding; however, they do not rule out alternative hypotheses of their functional consequences.…”
Section: Discussionmentioning
confidence: 99%
“…It would also have applications in biotechnology by providing a strategy to design mRNA transcripts rationally using synonymous codon mutations that maximize cotranslational folding while simultaneously minimizing misfolding for protein expression protocols 4,14 . For all these reasons, a number of studies have examined the role of codon usage across the entire genome of organisms [15][16][17] .…”
mentioning
confidence: 99%
“…Because some genes make more mRNA copies than others, we normalized for mRNA abundance and therefore the total number of codons actually decoded (Pechmann and Frydman 2013), using existing mRNA copy number data (Marguerat et al 2012). This too revealed tRNA Tyr to be the most limiting (Table 1, columns 5-6).…”
Section: Schizosaccharomyces Pombe Trnamentioning
confidence: 99%
“…We have used equation (2) to show that synonymous codons can switch yeast proteins between post-and co-translational folding mechanisms. Such quantitative modelling of co-translational folding opens up new opportunities to understand differential codon usage in organisms 31,46 , the influence of co-translational folding on mRNA sequence evolution 47 , and can form the basis for the rational design of mRNA sequences to manipulate nascent protein behaviour 48 .…”
Section: Discussionmentioning
confidence: 99%